Scaling laws in PZT thin films grown on Si(001) and Nb-Doped SrTiO3(001) substrates - Ramírez,J.-G. (2006)
A dynamic scaling and kinetic roughening study was done on digitized atomic force microscope (AFM) images of Pb(Zr0.52,Ti0.48)O3 (PZT) thin films. The films were grown on Si(001) and Nb - SrTiO3(001) (STNO) substrates via rf-sputtering technique at high oxygen pressures at substrate temperatures of 600 ºC by varying the deposition time and keeping other growth parameters fixed. By using a specific self-designed algorithm, we can extract from digitized 512-pixel resolution AFM-images, quantitative values of roughness parameters, i.e., interface width (sigma(l)), lateral correlation length (xi||) and, roughness exponent (alpha). Herein, we report on the sputter-time deposition dependence of the parameters describing roughness for both kinds of substrates. We report alpha-values for different time depositions (between 15 and 60 minutes) close to 0.55 for Si substrates and 0.63 for Nb - SrTiO3 substrates, indicating that the surface becomes more correlated in STNO substrates. The alpha-values are associated to the Lai-Das-Sarma-Villain model.